Questionário de Aceitação Ação para Professores - Galhardo, Ana (2019)
The Teachers Acceptance and Action Questionnaire (TAAQ) is a measure of teaching-related experiential avoidance (EA). The TAAQ for European Portuguese (TAAQ-PT) is a 15-item self-report instrument that revealed a single factor structure and a good fit to the data. Cronbach's alpha was .91. The TAAQ-PT showed to be a short, robust and reliable measure of teachers’ EA that can be used both in clinical and research settings.anagalhardo@ismt.pt